(untitled) (Global Media Journal - German Edition, 2022)
The article argues that the (new) media landscape of the European border regime rehearses colonial and slavocratic tropes often excised from canonical narratives of Fortress Europe, namely the fungibility of the other’s body and self. By discussing examples of (feigned) refugee self-representation, I demonstrate how the ostensible oppositionality of race and racial thinking (primitive past) and technology (modern future) fundamentally erodes in the European border regime while contributing to the further erasure of those most harshly targeted by it. The examined self-representations are caught in fungibility as the gaze of the other is circumvented by a proxy, instituting a relation of substitution that inherently depends on the erasure of the racialized subject for the purpose of white enjoyment.